Meningkatkan Aktivitas dan Hasil Belajar PPKn Menggunakan Model PBL, HOA, dan TS di SDN Telaga Biru 6 Banjarmasin - Norhamidah; Ahmad Muhyani Rizalie (Lembaga Pengembangan Kinerja Dosen, 2023)
The problems that occur in this study are the low activities and learning outcomes of Civics content, because learning is one-way, students have difficulty understanding the material, lack of activities that build a sense of cooperation, confidence and responsibility, lack of activities that require students to think critically, lack of student involvement actively in learning and the lack of learning activities that can develop student creativity. Efforts to overcome these problems are by using the PBL learning model, Hands On Activity and Talking Stick. The purpose of this research is to increase student learning activities and outcomes. The subjects of this study were fifth grade students at SDN Telaga Biru 6 Banjarmasin, which consisted of 30 students consisting of 12 boys and 18 girls. The method used is a qualitative approach with the type of PTK and using qualitative data obtained through observing the activities of educators and students, while quantitative data through student learning outcomes from individual written test results. These results show that the acquisition of educator activities at meeting IV obtained a score of 31 in the